Critical Thinking and Sustainability Awareness for PBL E-Module Development on Siak River Pollution - Sutini Sutini; Insih Wilujeng; Susilowati Susilowati (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2026)
This study aims to analyze junior high school students’ critical thinking skills and sustainability awareness as a basis for developing a Project-Based Learning (PBL) e-module on Siak River pollution. A mixed-methods descriptive design was employed involving 100 eighth-grade students from four schools in the Siak region. Quantitative data were collected using a critical thinking test and a sustainability awareness questionnaire, while qualitative data were obtained through classroom observations and teacher interviews. The results show that students’ critical thinking skills are low, with an average score of 40, particularly in evaluating and judging. Similarly, sustainability awareness is also low, with an average score of 39, especially in integrating sustainability values into daily behavior. Qualitative findings indicate that learning is still dominated by textbook-based and teacher-centered approaches, with limited integration of local environmental issues and minimal implementation of PBL. These findings suggest a gap between expected competencies and current practices. Therefore, the development of a PBL-based e-module integrating Siak River pollution is recommended to enhance students’ critical thinking and sustainability awareness through contextual and meaningful learning